A Bibliometric Analysis of 8271 Publications on Thyroid Nodules From 2000 to 2021 - Zhang, Qianqian; Xin, Xiaoyan; Wang, Li (Frontiers in Endocrinology, 2022)
Introduction: Thyroid nodules (TNs) are a common clinical disease. The probability of thyroid nodules being malignant is 7-15%. However, in recent decades, a number of publications on TNs have not been well summarized and discussed. The aim of this study was to summarize and sort out medical publications on TNs over the past 2 decades using a bibliometric method. Materials and Methods: Medical publications from January 1st, 2000, to November 1st, 2021, were searched in the Web of Science Core Collection database using the Medical Subject Heading (MeSH) term “thyroid nodule”. Full associated data were downloaded, and detailed information was extracted using the bibliometric analysis platform VOSviewer. Results: A total of 8271 publications related to TNs from the last 2 decades were found and included in this study. An increasing trend was presented in the annual number of publications. The United States, China and Italy contributed the most publications. Carcinoma, management, ultrasound, and fine-needle aspiration were the most popular subjects in the field of TNs. The topics of the studies could be stratified into four clusters. The first cluster was using ultrasound to evaluate the nodules, including the thyroid imaging reporting and data system (TI-RADS), elastography and benign features. The second cluster was the fine-needle aspiration method, including the Bethesda system, cytology and BRAF mutations. The third cluster was the management of nodules, including radiofrequency and thermal ablation, surgery, and consensus statements. The last cluster was carcinoma, which is correlated with all three clusters described above. The preoperative diagnosis of cytologically indeterminate nodules was particularly highlighted in the top 10 most cited publications in recent years. Conclusion: How to diagnose thyroid nodules as malignant or benign, especially in cytologically indeterminate nodules, is still the most concerning topic in TN research. Although the fine-needle aspiration method and gene-expression classifiers show promising results, there is still a crucial need for translations from fundamental studies to clinical applications.